Smoking prevalence in Portuguese school-aged adolescents - Sousa, Isabel (2013)
Due to the serious impact of smoking on children’s health – a higher risk of amygdalitis, flus, bronchitis, asthma attacks, as well as other respiratory problems – and its high prevalence, estimated in 8.8% worldwide, tobacco use is considered a pediatric epidemic. Several actions have been taken for its control, such as curriculum-based programs, environmental changes (smoking bans in schools and public places); parents’ involvement and strategies to limit tobacco access (restricted sale to young people, prohibition of sale in vending machines, creation of specific point of sale tobacco displays). According to the MPOWER approach, adopted by the WHO in 2008, monitoring tobacco use is needed as a tool to evaluate the effectiveness of the preventive measures developed for the control of tobacco use by adolescents and adults.